Manajemen Pengelolaan Perpustakaan di MTs Islahul Ummah NW Sukaraja - Izzudin, Ahmad; Aenul Apipah; Maulana Intan Fitriani; Dwi Trisna Sekar Nurti (Pendidikan Al-Gafari, 2024)
Library management is a study of what and how to do it, both through theory and practice, so that the library can be managed effectively and efficiently so that its presence among students is able to select, collect, manage, maintain information sources and provide services and added value for those who need them. The research aims to: 1) find out the role of the library for students, and 2) find out the management and development of the MTs Islahul Ummah NW Sukaraja library. This type of research is qualitative research with descriptive analysis methods. In collecting data, researchers used observation, interviews, and documentation methods. The validity of the researcher's data uses triangulation techniques. Data analysis was carried out in three stages, namely from the results of observations, interviews, and documentation. The conclusions of this research are 1) The role of the library for students, apart from being a learning resource center, the library is also a center for information and innovation, because students can take advantage of the existence of the library to search for information and can innovate through the existence of the library. Another role of libraries is also as a forum for educating the nation's generation. The school library has a very important role for students to improve students' knowledge and skills. With the establishment of a library, it can become a cheap, cheerful, and fast destination for realizing long-life education for students. 2) Management of the MTs Islahul Ummah NW Sukaraja school library continues to innovate and develop. Starting to carry out management in terms of improving the condition of the room, then adding books little by little, and then starting to collaborate and add partnerships. The MTs Islahul Ummah school library also continues to develop, starting by holding a reading interest library for students.